Parasite burden and reproductive success - Höjerslev, Monica (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2018)
Reproduction is fundamental for passing on genes and secure species survival. One crucial point of this is mate choice, mating with an unbeneficial partner, they risk less advantageous offspring than if a better mate had been chosen. To be able to make these choices, sexual signals, or ornaments, are very useful tools. Many studies have concluded the positive relationship between sexual signals and reproductive success, meaning that with better, brighter and more symmetric ornaments comes a higher reproductive success. Females are usually the ones that decide who is allowed to mate with them, therefore it is the males that carry ornaments. Additionally, studies have been made on how parasites can affect these ornaments but not many studies have covered the whole path, from parasite to reproductive success. For this work my main question is if there is any general correlation between parasite burden and reproductive success. Firstly, it is important to know some basic background about parasitism and how parasites can infect their host. Parasites are categorized in two ways, ecto- and endoparasites, i.e. parasites living on the surface respectively on the inside of the hosts’ body. One phylum of endoparasites has been mentioned more trequently than others among different studies - apicomplexans. The apicomplexan parasites presented in this work are Leucocytozoon spp. and Plasmodium spp. Additionally, one specific ectoparasite occurs, Carnus hemapterus, phylum arthropoda. Secondly, the effect of parasite infection on the host. Higher parasite burden takes energy and resources from the host who thereby cannot afford to invest as much in sexual signals or brightly colored ornaments. This will lead to lower chance for mating, it has been shown that ornaments play an important role in sexual selection and mate choice, they act as honest signals for quality. To summarize, a majority of the studies presented in this work point in the same direction and I can from them conclude that parasites most likely affect sexual signals negatively, leading to lower chance for mating and thereby lower reproductive success. Though, there are differences in opinion and some authors state that there is a positive correlation between parasite burden and sexual signals, in which case reproductive success would benefit.